PHOSPHORUS EFFECTS IN THE NUTRITION and GROWTH of DEVELOPING MANGO PLANTS - Renato, Prado de Mello [UNESP] (Taylor & Francis Inc, 2010)
The objective was to study the effects of phosphorous (P) fertilization on nutritional and developmental aspects of growing mango plants. The mango plants were evaluated by soil chemical analyses, leaf chemical analyses, biological examination of plant growth, and the starting point of fruit production. Having this in view, an experiment was set up on 2 January 2003, at Flora, a farm in Uberlandia, state of Minas Gerais, Brazil. The soil was a clayish Oxisol. The doses at planting were: D0 = zero, D1 = 40, D2 = 100, D3 = 200, and D4 = 300 g of P2O5 plant-1. These doses at the beginning of the second year were multiplied by 1.5 and at the beginning of the third year by 2.0 and applied to the plants. The fertilizer used in this experiment was triple superphosphate (44% of P2O5.). During August of 2004, 2005, and 2006, soil samples were taken at a depth of 20 cm in between the plant rows. Leaf samples were taken during August of 2004 and 2005 to determine macro- and micronutrient contents in the leaves. Plant stem diameter was measured during January of 2004 and 2005. Plant height and crown radius were measured during January of 2005 and fruit production in 2005 and 2006. Fertilizer applications increased the level of P in the soil but significantly influenced plant performance only after the second year. The effects of phosphorus on mango plants take place slowly leading to increments in plant stem diameter only at the third year. Fruit set was not influenced by phosphorous fertilization.
Keywords: Mangifera indica; nutrition of plant; phosphorous fertilization